Do high-skill immigrants raise productivity? Evidence from Israeli manufacturing firms, 1990-1999 - M. Daniele Paserman (IZA Journal of Migration, 2013)
This paper exploits the episode provided by the mass migration from the former Soviet Union to Israel in the 1990s to study the effect high skill immigration on productivity. Using a unique data set on manufacturing firms, I investigate directly whether firms and industries with a higher concentration of immigrants experienced increases in productivity. The analysis finds no correlation between immigrant concentration and productivity at the firm level in cross-sectional and pooled regressions. First-differences estimates reveal, if anything, a negative correlation between the change in output per worker and the change in the immigrant share. The immigrant share was strongly negatively correlated with productivity in low-tech industries. In high-technology industries, the results point to a positive relationship, hinting at complementarities between technology and the skilled immigrant workforce.
Keywords: J61; F22; D24; 330; immigration; productivity